DISSEMINATED FUNGAL INFECTION ON BONE MARROW TREPHINE IN AN ASPLENIC PATIENT - Qadir, Hira; Nida Qadir; Nadia Nasir; Areesha Qadir; Hammad Tanzeem (Journal of Ayub Medical College Abbottabad, 2021)
hyposplenism increases the risk of life-threatening infection with encapsulated bacteria. however, literature review revealed that hyposplenism is also a risk factor for disseminated fungal infection. here, we report a case of individual who presented with pyrexia of unknown origin and had splenectomy for hemolytic anemia and later he found to have disseminated fungal infection on bone marrow examination. this case emphasized the likelihood of disseminated fungal infection in an asplenic patient and also importance of bone marrow trephine in prompt diagnosis and management of patient.